Evaluation of Seismic Resilience of Self-Built Buildings through Nonlinear Analysis and Incremental Dynamic Analysis - Arriola Prieto, Cesar (2024)
This study, titled "Structural Vulnerability to Seismic Hazards in Housing in Zone X of Huaycán, Ate-Vitarte District, 2023," provides an in-depth evaluation of the seismic vulnerability of self-constructed housing within a highly seismic region of Lima. The methodology encompasses a comprehensive assessment of 2-, 4-, and 6-story residential buildings using compressive strength testing of concrete, which revealed a 30% deficiency relative to the E030 standard. To quantify collapse probabilities, advanced dynamic simulations and nonlinear analyses, including Incremental Dynamic Analysis (IDA), were conducted. The results indicate that 2- and 4-story structures are particularly susceptible, with an estimated collapse rate of 20.5% under extreme seismic conditions. Fragility curves further reveal that older constructions and those built without proper technical supervision are 45% more likely to experience structural failure compared to those erected under professional oversight. This underscores an urgent need for retrofitting interventions. Additionally, the study introduces a seismic resilience index aimed at quantifying the capacity of self-built housing to endure seismic events, providing a continuous assessment tool that supports enhanced construction practices and promotes the safety of vulnerable communities.